Advances in the Omicron variant development. (22nd March 2022) - Vitiello, Antonio; Ferrara, Francesco; Auti, Amogh M.; Di Domenico, Marina; Boccellino, Mariarosaria
Abstract: Severe acute respiratory syndrome coronavirus (SARS‐CoV)‐2 has spread worldwide, leading the World Health Organization (WHO) to declare a pandemic, on 11 March 2020. Variants of concern have appeared at regular intervals—Alpha, Beta, Gamma, Delta, and now Omicron. Omicron variant, first identified in Botswana in November 2021, is rapidly becoming the dominant circulating variant. In this review, we provide an overview regarding the molecular profile of the Omicron variant, epidemiology, transmissibility, the impact on vaccines, as well as vaccine escape, and finally, we report the pharmacological agents able to block the endocellular entry of SARS‐CoV‐2 or to inhibit its viral replication. The Omicron has more than 50 mutations, of which the spike protein has 26–35 amino acids different from the original SARS‐CoV‐2 virus or the Delta, some of which are associated with humoral immune escape potential and greater transmissibility. Omicron has a significant growth advantage over Delta, leading to rapid spread with higher incidence levels. The disease so far has been mild compared to the Delta. The two vaccination doses offer little or no protection against Omicron infection while the booster doses provide significant protection against mild illness and likely offer even greater levels of protection against serious illness. Recently, new oral antiviral agents such as molnupiravir and paxlovid have been approved and represent important therapeutic alternatives to antiviral remdesivir. In addition, monoclonal antibodies such as casirivimab/imdevimab bind different epitopes of the spike protein receptor; is this class of drugs effective against the Omicron variant? However, more research is needed to define whether Omicron is indeed more infectious and whether the vaccines, monoclonal antibodies, and antivirals currently available are effective. Abstract :